Consciousness and intentionality - Gillett, Grant, 1950- (Advances in consciousness research, 2001)
Is there an internal relationship between consciousness and intentionality? Can mental content be described in such a way so as to avoid dualism? What is the influence of social context upon consciousness, conceptions of self and mental content?This book considers questions such as these and argues for a conception of consciousness, mental content and intentionality that is anti-Cartesian in its major tenets. Focusing upon the rule governed nature of concepts and the grounding of the rules for concept use in the practical world, intentional consciousness emerges as a phenomena that depends upo.